Progression of disease within 24 months of initial therapy (POD24) detected incidentally in imaging does not necessarily indicate worse outcome. Issue 11 (18th September 2020) - Bitansky, Guy; Avigdor, Abraham; Vasilev, Elena; Zlotnick, Maya; Ribakovsky, Elena; Benjamini, Ohad; Nagler, Arnon; Kedmi, Meirav
Abstract: Progression of disease within 24 months of initial therapy (POD24) has previously been identified as a predictor of reduced overall survival (OS) for patients with follicular lymphoma (FL). Here we attempt to validate this finding in a retrospective cohort and understand whether the method by which progression is determined, clinically or radiographically, influences POD24 robustness. We reviewed records of 635 patients with FL and included 317 patients in our analysis. POD24 occurred in 21.5% of patients and it was evident that OS was significantly lower in the POD24 group. In multivariate analysis both POD24 and FLIPI were independently associated with inferior OS. POD24 that was detected by incidental routine imaging did not predict reduced OS as opposed to progression that was detected clinically. Although surveillance imaging is generally discouraged in FL, it still is a routine practice by many physicians, and therefore our findings are of significant clinical implications.